2007
DOI: 10.1016/j.imavis.2006.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor recognition at a distance by fusing gait and face

Abstract: We explore the possibility of using both face and gait in enhancing human recognition at a distance performance in outdoor conditions. Although the individual performance of gait and face based biometrics at a distance under outdoor illumination conditions, walking surface changes, and time variations are poor, we show that recognition performance is significantly enhanced by combination of face and gait. For gait, we present a new recognition scheme that relies on computing distances based on selected, discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…However, direct template matching has been shown to be sensitive to noise and small silhouette distortions by previous studies [6], [12] as well as our experiments (see Section V). To overcome this problem, statistical feature learning based on subspace Component and Discriminant Analysis (CDA) can be employed to further reduce the feature dimensionality [7].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, direct template matching has been shown to be sensitive to noise and small silhouette distortions by previous studies [6], [12] as well as our experiments (see Section V). To overcome this problem, statistical feature learning based on subspace Component and Discriminant Analysis (CDA) can be employed to further reduce the feature dimensionality [7].…”
Section: Introductionmentioning
confidence: 54%
“…However, direct template matching has been shown to be sensitive to noise and small silhouette distortions [6], [12]. This is because that the dimensionality of the GEI feature space is high even after feature selection (typically in the order of thousands).…”
Section: Adaptive Component and Discriminant Analysismentioning
confidence: 99%
“…In [41], Kale et al showed that even in single camera environment, directly combining the scores of face and gait can boost the overall performance. Based on population Hidden Markov model (pHMM), Liu and Sarkar selected gait stances for recognition in the outdoor environment [49]. Extensive experimental results were reported on handling variations in the walking surface and elapsed time covariates, based on different fusion strategies.…”
Section: Fusing Gait and Facementioning
confidence: 99%
“…Extensive experimental results were reported on handling variations in the walking surface and elapsed time covariates, based on different fusion strategies. They found performance is higher when fusing gait and face than intra-model fusion (i.e., face+face or gait+gait) [49]. By claiming that the reliability of face and gait varies with different subject-camera distances, Geng et al proposed an adaptive score-level fusion scheme [15].…”
Section: Fusing Gait and Facementioning
confidence: 99%
“…Some of the benefits are that it is non-invasive, perceivable at a distance, easy to set up in public area and can be hard to conceal [11]. Gait can also be used in fusion with other biometrics to enhance the overall performance [6].…”
Section: Introductionmentioning
confidence: 99%